The New History of Uzbekistan Picture Style, Problems and Solutions of National Painting Composition Methodology and Technology of Architectural Architecture Projects - Ro’zikhon Djalilova Kazakovna (Scientific Trends, 2023)
Various projects in architectural ensembles, painting, pottery art, style, principles, methodology, sketching drawings, pencil drawing, history of painting technology. The importance and significance of the buildings of the 19th and 21st centuries, the buildings of the neighborhood, the palace, the wall, and the monumental images of the palace walls as a scientific and practical education for the youth of the present time were discussed.
Keywords: Painting, art, history, grix, kundal, Frontal composition, chromatic colors, linear perspective, Deep spatial composition, Private shadow, Hatching, Emblem, Final decoration, Penumbral, complementary colors, Drafting, volumetric compositions Size (relief ) perspective, volumetric compositions, volume (relief) perspective.